THE ROLE OF A HUMAN FACTOR IN FORMATION RISKS OF DESTRUCTIVE CHANGES IN A BUSINESS CYCLE OF A COMPANY - P. V. Ushanov (Real Economics Publishing House, 2014)
In the article the nature of a human factor is considered as an economic category, the influence of the human factor on a business cycle of companies is studied, business cycle’s phases are determined. Besides that the author investigates risks of destructive changes in business activity of an object of management that are caused by business cycle phases’ changes.